Persepsi Tentang Fungsi Pendidikan Anak Sebagai Faktor Mobilitas Sosial di Masa Depan di Lingkungan Keluarga Muslim - Tim LP3 (LP3 UMY, 2015)
This research on the Perception on Children Eclucation as a Social Mobility Factor in the Future in a Moslem Family is based on the need to depict how a Moslem familv chooses an etlucation for its children. In Indonesia, a Moslemfamily has two choices on lhe rype of educulion. i. e , general (Western originated) schr:ol and pesantren (lslumic conventionul sy.\tem ofeducalion). These types differ in lheir value sv.\tem. objec Iives, methods. end post-education orientation.